An Estimated Small Open Economy Model of the Financial Accelerator - Justiniano Espigares, Alejandro (IMF Working Papers; Working Paper ;, 2005)
This paper develops a small open economy model where entrepreneurs partially finance investment using foreign currency denominated debt subject to a risk premium above and beyond international interest rates. We use Bayesian estimation techniques to evaluate the importance of balance sheet vulnerabilities combined with the presence of the financial accelerator for emerging market countries. Using Korean data, we obtain an estimate for the external risk premium, indicating the importance of the financial accelerator and potential balance sheet vulnerabilities for macroeconomic fluctuations. Furthermore, our estimates of the Taylor rule imply a strong preference to smooth both exchange rate and interest rate fluctuations.